CRITERIA AND INDICATORS FOR THE DEVELOPMENT OF THE CREATIVE COMPETENCE OF THE SCHOOL TEACHER (Web of Teachers: Inderscience Research, 2023)
This article describes the issues of the need to improve creativity among students of general education schools, the ideas of deepening the theoretical aspects of the formation of scientific and practical knowledge in general education schools and raising the effectiveness of education to the quality level.